2011
DOI: 10.1038/onc.2011.426
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin regulates the MAPK kinase pathway to induce increased expression of DNA repair gene ERCC1 and increase melanoma chemoresistance

Abstract: The incidence of malignant melanoma is growing rapidly worldwide and there is still no effective therapy for metastatic disease. Melanoma is the second most common cancer among young adults in the UK, where incidence rates have more than quadrupled since the 1970s. Increased expression of a number of DNA repair genes has been reported in melanoma and this likely contributes to its extreme resistance to conventional DNA-damaging chemotherapeutics. One such chemotherapeutic that is effective against a range of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 47 publications
(57 reference statements)
3
67
0
1
Order By: Relevance
“…Of great interest was how ILK modulated these molecules. It has been shown that the expression of ERCC1 (Li et al, 2012) and GST-π (Zhang et al, 2009) is regulated by MAPK/ ERK pathway, and the RhoE has a direct interaction with ILK (Pereira et al, 2009;Berti et al, 2011). The western blotting results confirmed that the phosphorylation of ERK was attenuated by ILK silencing, which might result in the negative regulation of ERCC1 and GST-π.…”
Section: Discussionsupporting
confidence: 63%
“…Of great interest was how ILK modulated these molecules. It has been shown that the expression of ERCC1 (Li et al, 2012) and GST-π (Zhang et al, 2009) is regulated by MAPK/ ERK pathway, and the RhoE has a direct interaction with ILK (Pereira et al, 2009;Berti et al, 2011). The western blotting results confirmed that the phosphorylation of ERK was attenuated by ILK silencing, which might result in the negative regulation of ERCC1 and GST-π.…”
Section: Discussionsupporting
confidence: 63%
“…Malignant melanoma incidence is rapidly increasing and has almost doubled in the previous decade (2). Whilst DTIC chemotherapy is the standard treatment, <20% of patients respond at all to the treatment and <5% continue to respond to long-term treatment (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the 10-year survival rate of patients diagnosed with advanced (stage IV) metastatic melanoma is <10% (2), which highlights the importance of early detection and treatment. The Food and Drug Administration approved the chemotherapeutic agent dacarbazine (DTIC) for the treatment of metastatic melanoma in 1975, and it remains the only licensed chemotherapeutic agent in use today (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, the emergence of drug resistance results in the failure of chemotherapy. Various studies have revealed that the phosphoinositide 3-kinase (PI3K), mitogen-activated protein kinases (MAPKs) pathways, Bax-like proteins, and Bcl2-like proteins are involved in cisplatin resistance [7][8][9][10]. Therefore, new strategies, such as the combination of natural products and chemotherapy agents, are needed to overcome cisplatin resistance or sensitize tumor cells to cisplatin.…”
Section: Introductionmentioning
confidence: 99%